Racial identity as a moderator of the association between socioeconomic status and quality of life - Adedeji, Adekunle; Buchcik, Johanna; Akintunde, Tosin Yinka; Idemudia, Erhabor S. (Frontiers in Sociology, 2022)
Research in social and humanitarian science has identified socioeconomic status (SES) as one of the essential determinants of quality of life (QoL). Similarly, racial identity is assumed to predict SES outcomes in multiracial settings. Therefore, understanding how racial identity moderates the association between SES and QoL may provide essential insights into the mechanisms generating socioeconomic inequalities and their implication on life outcomes. The current study employs a cross-sectional study designed to investigate the moderating effect of racial identity on the association between SES and QoL in a sample of 1,049 South Africans. A correlation matrix was computed to explore the bivariate associations between QoL, socioeconomic, and sociodemographic features. ANOVA was used to evaluate racial differences in QoL and SES. A moderator analysis was adopted to determine a possible moderating effect of racial identity on the connection between SES and QoL. Findings show a significant difference in QoL and SES based on race. While racial identity was a significant moderator of the association between QoL and SES for Black Africans, no significant moderating effect was reported for other racial groups. These results highlight the importance of racial identity for life outcomes and emphasis the unique experience associated with Black racial identity and its implications for SES, QoL, and their association in South Africa. This study explains the necessity to improve the QoL of minority groups, such as Black South Africans, and offers detailed explanations of their perceived disadvantage.